1991
DOI: 10.1093/ajh/4.8.680
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefit of Captopril in Salt-Loaded Stroke-Prone Spontaneously Hypertensive Rats Is Independent of Hypotensive Effect

Abstract: In the present study we examined whether the angiotensin I converting enzyme inhibitor, captopril, would protect stroke-prone spontaneously hypertensive rats (SHRSP) from stroke and renal pathology over a 26-week period. In the control group of six untreated SHRSP fed Stroke-Prone Rodent Diet and 1% NaCl drinking solution, all animals developed severe hypertension and stroke by 16.1 weeks of age. In eight salt-loaded SHRSP treated with oral captopril (50 mg/kg/day) beginning at 8.4 weeks of age, systolic blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
58
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 3 publications
5
58
0
Order By: Relevance
“…Thus, our data confirm previous findings in reports demonstrating the cardioprotective action of RAS inhibition in hypertensive rats on a salt excess diet (14,18,33). It reflected decreased LV collagen deposition in treated salt-loaded rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, our data confirm previous findings in reports demonstrating the cardioprotective action of RAS inhibition in hypertensive rats on a salt excess diet (14,18,33). It reflected decreased LV collagen deposition in treated salt-loaded rats.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in addition to its hemodynamic effects, dietary salt excess exerts additional nonpressure-related cardiac effects in different forms of experimental and human essential hypertension (5-7, 12, 13, 24, 26, 43). Various mechanisms have been suggested to explain these adverse cardiovascular effects of dietary salt excess, and some evidence supports the role of the renin-angiotensin system (RAS) in their development (18,21,33,36,45).…”
mentioning
confidence: 99%
“…In stroke-prone hypertensive rats, di- minishing RAS activity with potassium, 24 captopril, 25 or losartan 26,27 prevented stroke occurrence without lowering blood pressure. Moreover, studies in a model of acute stroke induced by carotid ligation in gerbils suggest that AT 2 receptor stimulation may mediate cerebrovascular anti-ischemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Support for this concept comes from clinical trials demonstrating that treatment of hypertensive patients with either angiotensin-converting enzyme (ACE) inhibitors (38, 53) or ANG II type 1 (AT 1 ) receptor blockers (41, 60) provides significant protection from, and even reversal of, end-organ damage. Animal studies have also demonstrated that ACE inhibitors and AT 1 receptor antagonists prevent cardiovascular injury (23,55,56) as well as protect against renal (3, 55, 57) and cerebral (55-57) injury.The use of these antagonists of the RAAS not only reduces the formation and actions of ANG II but also results in a significant elevation of another fragment of the RAAS, angiotensin- …”
mentioning
confidence: 99%
“…tagonists prevent cardiovascular injury (23,55,56) as well as protect against renal (3,55,57) and cerebral (55)(56)(57) injury.…”
mentioning
confidence: 99%